Broad Neutralization Responses Against Oncogenic Human Papillomaviruses Induced by a Minor Capsid L2 Polytope Genetically Incorporated Into Bacterial Ferritin Nanoparticles - Yang, Fan; Mariz, Filipe C.; Zhao, Xueer; Spagnoli, Gloria; Ottonello, Simone; Müller, Martin (Frontiers in Immunology, 2020)
Cervical cancer remains a global health burden despite the introduction of highly effective vaccines for the prophylaxis of causative human papillomavirus infection (HPV). Current efforts to eradicate cervical cancer focus on the development of broadly protective, cost-effective approaches. HPV minor capsid protein L2 is being recognized as a promising alternative to the major capsid protein L1 because of its ability to induce responses against a wider range of different HPV types. However, a major limitation of L2 as a source of cross-neutralizing epitopes is its lower immunogenicity compared to L1. Various approaches have been proposed to overcome this limitation, we developed and tested ferritin-based bio-nanoparticles displaying tandemly repeated L2 epitopes from eight different HPV types grafted onto the surface of Pyrococcus furiosus thioredoxin (PfTrx). Genetic fusion of the PfTrx-L2(8x) module to P. furiosus ferritin (PfFe) did not interfere with ferritin self-assembly into an octahedral structure composed by 24 protomers. In guinea pigs and mice, the ferritin super-scaffolded, L2 antigen induced a broadly neutralizing antibody response covering 14 oncogenic and two non-oncogenic HPV types. Immune-responsiveness lasted for at least one year and the resulting antibodies also conferred protection in a cervico-vaginal mouse model of HPV infection. Given the broad organism distribution of thioredoxin and ferritin, we also verified the lack of cross-reactivity of the antibodies elicited against the scaffolds with human thioredoxin or ferritin. Altogether, the results of this study point to Pyrococcus furiosus ferritin nanoparticles as a robust platform for the construction of peptide-epitope-based HPV vaccines.